Health Assessment Questionnaire at One Year Predicts All‐Cause Mortality in Patients With Early Rheumatoid Arthritis. Issue 2 (29th December 2020) - Fatima, Safoora; Schieir, O.; Valois, M. F.; Bartlett, S. J.; Bessette, L.; Boire, G.; Hazlewood, G.; Hitchon, C.; Keystone, E. C.; Tin, D.; Thorne, C.; Bykerk, V. P.; et al.
Abstract : Objective: Higher self‐reported disability (high Health Assessment Questionnaire [HAQ] score) has been associated with hospitalizations and mortality in established rheumatoid arthritis (RA), but associations in early RA are unknown. Methods: Patients with early RA (symptom duration <1 year) enrolled in the Canadian Early Arthritis Cohort who initiated disease‐modifying antirheumatic drugs and had completed HAQ data at baseline and 1 year were included in the study. Discrete‐time proportional hazards models were used to estimate crude and multi‐adjusted associations of baseline HAQ and HAQ at 1 year with all‐cause mortality in each year of follow‐up. Results: A total of 1, 724 patients with early RA were included. The mean age was 55 years, and 72% were women. Over 10 years, 62 deaths (3.6%) were recorded. Deceased patients had higher HAQ scores at baseline (mean ± SD 1.2 ± 0.7) and at 1 year (0.9 ± 0.7) than living patients (1.0 ± 0.7 and 0.5 ± 0.6, respectively; P < 0.001). Disease Activity Score in 28 joints (DAS28) was higher in deceased versus living patients at baseline (mean ± SD 5.4 ± 1.3 versus 4.9 ± 1.4) and at 1 year (mean ± SD 3.6 ± 1.4 versus 2.8 ± 1.4) ( P < 0.001). Older age, male sex, lower education level, smoking, more comorbidities, higher baseline DAS28, and glucocorticoid use were associated with mortality. Contrary to HAQ score at baseline, the association between all‐cause mortality and HAQ score at 1 year remained significant even after adjustment for confounders. For baseline HAQ score, the unadjusted hazard ratio (HR) was 1.46 (95% confidence interval [95% CI] 1.02–2.09), and the adjusted HR was 1.25 (95% CI 0.81–1.94). For HAQ score at 1 year, the unadjusted HR was 2.58 (95% CI 1.78–3.72), and the adjusted HR was 1.75 (95% CI 1.10–2.77). Conclusion: Our findings indicate that higher HAQ score and DAS28 at 1 year are significantly associated with all‐cause mortality in a large early RA cohort.